Rancang Bangun Alat Pengolah Limbah Plastik Berbahan Bakar Biomassa - Pribadyo Pribadyo; Teguh Firmanto (universitas teuku umar, 2018)
Plastic is a material that is widely used in daily life, because it has advantages such as strong, lightweight and stable. But the plastic on the market today are synthetic polymers made from petroleum are difficult to decompose in nature. Judging from the nature of the plastic constituent is composed of components of petroleum hydrocarbons, the plastic waste has the potential to be converted into fuel. The technique used to restore the plastic material is by breaking the carbon chains or polymers that become hydrocarbons. The purpose of the design tool processing waste plastics into fuel oilfired biomass is to design a waste treatment plant in the plastic to produce oil (fuel), making the design drawings of the equipment is planned, determine the materials to be used, make and assemble the apparatus according to the design the planned. In pyrolysis occurs tool decomposition process of organic compounds on the materials. This decomposition caused by the heating process without dealing directly with the air with little oxygen. Waste processing equipment plastic that will be planned to include the design of the combustion chamber, reactor design, pipeline design fence steam, design connecting pipe between the reactor and the pipe fence steam. Extensive volume of reactor tubes obtained then has acquired equipment capacity 4 kg / production. Keywords: plastic waste, biomass, pyrolysis, design, oil